Implication of basal lamina dependency in survival of Nrf2‐null muscle stem cells via an antioxidative‐independent mechanism. Issue 2 (2nd August 2018) - Takemoto, Yusei; Inaba, Shoya; Zhang, Lidan; Tsujikawa, Kazutake; Uezumi, Akiyoshi; Fukada, So‐ichiro
Abstract : Nuclear factor erythroid 2–related factor 2 (Nrf2) is a master regulator for the induction of antioxidative genes and plays roles in diverse cellular functions. The roles of Nrf2 in muscle regeneration have been investigated, and both important and unimportant roles of Nrf2 for muscle regeneration have been reported. Here, using aged Nrf2‐null and Nrf2–dystrophic double‐null mice, we showed nonsignificant phenotypes in the muscle regeneration ability of Nrf2‐null mice. In contrast with these results, strikingly, almost all Nrf2‐null muscle stem cells (MuSCs) isolated by fluorescence‐activated cell sorting died in vitro of apoptosis and were not rescued by antioxidative reagents. Although their proliferation was still impaired, the Nrf2‐null MuSCs attached to myofibers activated and divided normally, at least in the first round. To elucidate these discrepancies of MuSCs behaviors, we focused on the basal lamina, because both in vivo and single myofiber culture allow MuSCs within the basal lamina to become activated. In a basal lamina–disrupted model, Nrf2‐null mice exhibited remarkable regeneration defects without increased levels of reactive oxidative species in MuSCs, suggesting that the existence of the basal lamina affects the survival of Nrf2‐null MuSCs. Taken together, these results suggest that the basal lamina compensates for the loss of Nrf2, independent of the antioxidative roles of Nrf2. In addition, experimental conditions might explain the discrepant results of Nrf2‐null regenerative ability. Abstract : Muscle regeneration ability of Nrf2‐null mice is normal. However, in a basal lamina–disrupted model, Nrf2‐null mice exhibited remarkable regeneration defects without increased levels of reactive oxidative species in muscle stem cells